Breast-feeding and respiratory syncytial virus infection. Issue 6247 (18th October 1980) - Pullan, C R; Toms, G L; Martin, A J; Gardner, P S; Webb, J K; Appleton, D R
Abstract : The pattern of breast-feeding in 127 infants admitted to hospital with respiratory syncytial virus infection was compared with that in 503 age-matched controls. Thirty per cent of children with infection had been breast-fed compared with 49% of controls. The approximate relative risk of being admitted to hospital with respiratory syncytial virus infection if not breast-fed was 2.2. Several other factors were also considered, including an assessment of maternal care and home environment; the mother's age, marital state, and smoking habits; the number of siblings; and gestation. Adverse factors were all associated with an increased risk of admission with infection, but breast-feeding still appeared to provide protection after controlling for these other factors in turn. These findings provide further support for encouraging mothers to breast-feed their infants and should prompt further studies into the immune status of mothers and into the nature of the protective factors in their breast milk.